The Influence of Self Assessment System on Taxpayer Compliance in Reporting SPT OP at Bogor Primary Tax Service Office - Vega, Armelia; Mulyana Dali, Rahmat; Yudiana, Yudiana (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
The self-assessment system is one of the collection systems implemented in Indonesia, this system requires people to register themselves as taxpayers at the Tax Service Office according to their domicile independently, as well as carry out other tax obligations independently as well as calculating, paying and reporting taxes in a different tax year. already lived. The elements that influence compliance are the taxpayers' understanding of how to fulfill their tax obligations. The easier it is for taxpayers to understand tax laws, the easier it is for them to comply with their tax obligations. The data collection technique follows the procedure used to obtain data by providing a piece of paper (questionnaire). One person who is willing to express his opinion in accordance with the questions asked is given a series of choices or comments in the form of a statement which will be given later only requiring a tick in the appropriate column and including the question and identity of each respondent. Based on the subtest results, a significance value gives a numerical value of 0.00 which is smaller than the decision criterion, which is 0.05, meaning that the x variable in this study, namely the self-rating system, has an effect on To do. the variable y is compliance with tax obligations when reporting SPT OP. Responsibilities When Reporting SPT OP. Based on the results of the research that has been done, the conclusion in this study is that the self-assessment system has proven to have a positive effect on taxpayer compliance in reporting SPT OP. Supported by data obtained from KPP Pratama Bogor, that there was an increase from the previous year in reporting SPT OP. This states that the higher the taxpayer's understanding of the self-assessment system, the taxpayer's compliance in reporting SPT will also increase.